2007
DOI: 10.1016/j.vaccine.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Development and preclinical evaluation of an alphavirus replicon particle vaccine for cytomegalovirus

Abstract: We used a replication-incompetent, single-cycle, alphavirus replicon vector system to produce viruslike replicon particles (VRP) expressing the extracellular domain of human cytomegalovirus (CMV) glycoprotein B or a pp65/IE1 fusion protein. Efficient production methods were scaled to produce pilot lots and clinical lots of each alphavirus replicon vaccine component. The vaccine induced hightitered antibody responses in mice and rabbits, as measured by ELISA and CMV neutralization assays, and robust T-cell resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Using an alphavirus replicon vaccine based on Venezuelan equine encephalitis (VEE) virus and consisting of virus replicon particles (VRPs) expressing gB and a pp65-IE1 fusion protein, vaccine candidates were found to be immunogenic in mice [99] and humans [100]. When VRPs encoding gH/ gL or PC were compared with the two complexes in the presence or absence of MF59 adjuvant, it was found that VRPs expressing PC produced higher levels of Nt antibodies than those expressing gH/gL, and that MF59 significantly increased the potency of each complex [101,102].…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…Using an alphavirus replicon vaccine based on Venezuelan equine encephalitis (VEE) virus and consisting of virus replicon particles (VRPs) expressing gB and a pp65-IE1 fusion protein, vaccine candidates were found to be immunogenic in mice [99] and humans [100]. When VRPs encoding gH/ gL or PC were compared with the two complexes in the presence or absence of MF59 adjuvant, it was found that VRPs expressing PC produced higher levels of Nt antibodies than those expressing gH/gL, and that MF59 significantly increased the potency of each complex [101,102].…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…challenge with EBOV using VRP expressing EBOV GP or NP proved unsuccessful (31). Subsequent studies were carried out using higher doses of VRP vaccine, made possible by improvements in VRP manufacturing and downstream processing (32)(33)(34)(35). Here, we report that VRPs expressing EBOV GP or SUDV GP can elicit immune responses that are sufficient to protect NHPs against, not only i.m.…”
mentioning
confidence: 94%
“…Most importantly, recombinant alphaviruses provide a platform that has been shown to elicit protec- tive Ab responses against many diverse pathogens in preclinical models (15,22,36,44,48). In one key example, protection of both juvenile and infant rhesus macaques against measles virus was achieved after a single intradermal dose of recombinant VEE/SIN VRP expressing measles virus hemagglutinin (35).…”
Section: Discussionmentioning
confidence: 99%
“…The chimeric (VEE/SIN) alpha-virus vector system used in this study was derived from Venezuelan equine encephalitis virus (VEE) and the Sindbis virus (SIN). The recombinant VEE, SIN, and Semliki viruses expressing SIV or HIV antigens as well as antigens from a diverse and growing list of pathogens have been evaluated extensively in animals by several groups (6,15,16,17,22,32,34,35,36,38,42,44,57,58). The chimeric alphavirus replicon particles (VRP) used here were designed to combine the immune potency of the VEE replicon with the safety profile of the SIN structural proteins (38).…”
mentioning
confidence: 99%